(untitled) (Research, Society and Development, 2021)
This study of pedagogical practice evidenced the planning adopted during the teaching internship held in the second semester of the course of Formação Pedagógica para Graduados não Licenciados do Instituto Federal Sul-rio-grandense – Câmpus Pelotas, carried out in a class of the Integrated Technical Course in Visual Communication, in the Marketing and Packaging discipline. The proposal of this pedagogical intervention focused on a teaching practice that focused on learning from content that made sense to the student. The theoretical perspective used, with a Marxist background, was based on the bias of the Progressive Tendency “Social-Critical of Content” (Libâneo, 1994). The core of the proposal found an echo in Vygotsky’s theory (1984), stating that the construction of knowledge, disposed in an action of sharing, in a process of mediation between subjects, aiming not to isolate an educational fact from the sociocultural situation of the student. The performance was concluded from a socio-constructivist, interactionist perspective, in which the use of information and development of teaching and learning, in the light of didactics, enhancing educational processes in an omnilateral way, intending that students would be able to enjoy science, art and technique.